The Concept of Structural Legal Aid in Combating Corruption from the Maqashid Shariah Perspective - Hidayat, Hidayat; Tanjung, Dhiauddin; Harahap, Mhd. Yadi (Universitas Nurul Jadid, 2024)
Corruption poses a severe threat to societal well-being, as it undermines various sectors such as education, economy, and law. Consequently, combating corruption effectively is imperative. This study aims to analyze and elucidate efficient strategies for corruption eradication, specifically through the concept of structural legal aid with a maqasid sharia approach. Employing a juridical-normative research methodology, this research integrates statutory, case, and conceptual analyses. Primary legal resources including laws, books, and journals are utilized, supplemented by interviews with key stakeholders such as the Indonesian Legal Aid Foundation (YLBHI) and MUI Medan City, alongside observations at the People's Basic Rights Advocacy Center (SAHdaR). Findings indicate that the structural legal aid framework prioritizes community engagement in combating corruption. Furthermore, by incorporating the maqasid sharia approach, this framework is deemed effective, as it not only fosters community involvement but also enhances public awareness regarding the perils of corruption. Consequently, this approach serves to safeguard state finances, ensure equitable punishment for offenders, and uphold the fundamental rights of citizens, who are often the primary victims of corruption.